Perinatal Outcome of Deliveries after One Previous Caesarean Section: A Prospective Study from Mid-west hilly Nepal - Kaur, Narinder; Jain, Sushila (Journal of Lumbini Medical College, 2016)
Introduction: Contrary to the WHO recommended caesarean section (CS) rate of 15%, there is an alarming trend of increasing caesarean section rates. An important reason for this is repeat caesarean section (RCS). Vaginal birth after caesarean (VBAC) is one of the methods of reducing CS rates in women with history of previous CS. This study was done with the aim to see the maternal and fetal outcome among parturient with history of single previous caesarean section and to determine the rate of VBAC at Lumbini Medical College, Nepal. Methods: This is a prospective study done for a period of ten months. Seventy parturient fulfilling inclusion criteria of term pregnancy with single live fetus and history of one Lower Segment Caesarean Section (LSCS) were enrolled in the study. Patients meeting the criteria for VBAC were given trial of labour and others were taken for elective repeat CS. This cohort was analyzed further, with respect to age, parity, period of gestation, mode of delivery, indication for CS, maternal and fetal complications and outcomes. Results: VBAC was successful in 27.14% of patients (n=19) while the rest 51 (72.85%) underwent RCS . Indications for RCS was mainly scar tenderness 7 (13.7%), fetal distress 6 (11.7%), non progress of labour 6 (11.7%), meconium stained liquor 6 (11.7%) and post-dated pregnancy 6 (11.7%). Maternal morbidity was comparable in women undergoing RCS or VBAC. There was one still birth and one early neonatal death in each group due to complications of meconium aspiration. Conclusion: Patients with previous CS are at high risk of RCS. If trial of labor is allowed under careful patient selection and supervision, the rate of vaginal delivery after caesarean section can be increased safely. As there is no added perinatal morbidity and mortality in cases of VBAC as compared to RCS, VBAC shows the right way forward to decrease the rate of caesarean section. DOI: https://doi.org/10.22502/jlmc.v3i1.64